Connecting Metabolism to Mastitis: Hyperketonemia Impaired Mammary Gland Defenses During a Streptococcus uberis Challenge in Dairy Cattle - Swartz, Turner H.; Bradford, Barry J.; Mamedova, Laman K. (Frontiers in Immunology, 2021)
β-hydroxybutyrate (BHB) has been associated with disease incidence in early lactation dairy cattle, but such associations do not demonstrate causation. Therefore, the objective of this study was to examine the effects of BHB during an intramammary Streptococcus uberis challenge. A secondary objective was to elucidate the mechanisms behind BHB effects on cytokine transcript abundance using the RAW 264.7 cell line. Late lactation multiparous dairy cows (n = 12) were continuously infused intravenously with either BHB to induce hyperketonemia (target concentration: 1.8 mM) or with saline (CON) for 72 h during a S. uberis intramammary challenge. Body temperature, dry matter intake (DMI), milk production, and milk S. uberis cfu were measured daily until one week post-challenge. Blood samples were collected during infusion to assess changes in metabolism (glucose, insulin, glucagon, NEFA, and cortisol) and systemic inflammation (IL-1β and SAA). Mammary biopsies were conducted at 72-h post-challenge to assess transcript abundance of inflammation-associated genes. BHB-infused cows exhibited a delayed febrile response, noted by a lesser vaginal temperature during the final day of infusion, followed by a greater vaginal temperature 6 d post-challenge. Consequently, BHB-infused cows had greater S. uberis cfu on d 4, 6, and 7 as compared to CON. Accordingly, BHB-infused cows consumed less DM, produced less milk, reduced blood glucose, and increased cortisol concentrations, however, no effects were seen on other systemic parameters or transcript abundance of inflammation-related genes in mammary tissue. To elucidate mechanisms behind the impaired immune defenses, RAW 264.7 cells were transfected with a GPR109A siRNA for 24 h and then treated with or without 1.8 mM BHB and challenged or left unchallenged with S. uberis for an additional 3 h. Transfection with siRNA reduced Gpr109a by 75%. Although BHB treatment did not significantly increase Il10, GPR109A knockdown as compared to the scrambled control reduced Il10 by 90% in S. uberis challenged macrophages treated with BHB, suggesting that macrophage immune responses to S. uberis can be altered via a GPR109A-dependent mechanism. Taken together, these data suggest that BHB altered the immune response promoting tolerance toward S. uberis rather than resistance.